Trehalose Study Medicinal Properties Isolated from Tobacco Plants and Treatment of a-Crystallin Diseases - Rezvani, Sahar (Asian Journal of Chemistry, 2012)
Tobacco is an agricultural product processed from the leaves of plants in the genus Nicotiana. It can be consumed, used as an organic pesticide and, in the form of nicotine tartrate, used in some medicines. Trehalose, a simple disaccharide, has been shown to be effective in preventing the deactivation of numerous proteins and in protecting cells against stress. This study and analysis of trehalose from leaves of Nicotiana tobacum show some diseases that will be better with using by trehalose. In this study, tobacco (Nicotiana tobacum L.C.V E1) was analyzed for the presence of trehalose. Using gas chromatography-mass spectrometry (GC-MS) analysis, trehalose was unambiguously identified in extracts from leaves Nicotiana tabacum. So, it was found that trehalose had accumulated in leaves.